THE BUTEYKO BREATHING TECHNIQUE IN STABILIZING RESPIRATORY RATE AND CONTROL PAUSES IN BRONCHIAL ASTHMA PATIENTS: CASE STUDY - Septina Isna Ifanda; Agis Taufik; Iwan Purnawan (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Introduction: Asthma is a chronic inflammatory disease of the airways that causes hyperresponsiveness and narrowing of the airways, with symptoms such as shortness of breath, wheezing, and coughing that can appear suddenly. Asthma management requires a comprehensive approach, including pharmacological and non-pharmacological therapies. The buteyko breathing technique is one of the effective non-pharmacological interventions to control asthma symptoms, reduce the frequency of attacks, and improve quality of life without side effects. This study aims to implement the buteyko breathing technique to stabilize respiratory frequency in patients with bronchial asthma. Purpose: This case study is to determine the effectiveness of buteyko therapy in stabilizing respiratory rates and control pauses in bronchial asthma patients. Methods: The method used in this study is a case study with 3 asthma patients as subjects. The focus of this study is evidence-based practice in the form of buteyko breathing therapy for 3 days and is carried out 3 times a day. Discussion: The results of the study showed that the buteyko breathing technique can stabilize the respiratory rate in bronchial asthma patients. Conclusion: Buteyko breathing technique can help stabilize respiratory rate in asthma patients, although the results are not statistically significant. These results indicate that buteyko breathing technique has the potential to prolong the duration of control pauses, which may support improved respiratory control in asthma patients.